Pengaruh Social Media dan Brand Ambasador Terhadap Minta Beli Produk Glad2glow Pada Missglam - Heni Anjelica Silalahi; Juliana Br Sagala; Septiana Lumbangaol; Toman Sony Tambunan (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to analyze the influence of social media marketing and brand ambassadors on the purchase interest of Glad2Glow products on MissGlam. The development of digital technology has influenced the way companies market their products, especially through social media platforms. This study uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to 100 respondents who are active social media users and MissGlam customers. Data analysis was carried out using multiple linear regression to test the influence of each independent variable on product purchase interest. The results of the study show that both social media marketing and brand ambassadors have a positive and significant influence on the purchase interest of Glad2Glow products. Social media marketing, with interesting content and promotion through digital platforms, has a strong impact on building awareness and purchase interest. In addition, the presence of brand ambassadors who have influence on the audience also plays an important role in increasing consumer purchasing decisions. These findings provide implications for companies to further maximize digital marketing strategies and choose the right brand ambassadors to increase product purchase interest in a competitive market.